1997
DOI: 10.2118/30978-pa
|View full text |Cite
|
Sign up to set email alerts
|

Permeability Determination From Well Log Data

Abstract: We discuss and compare three different approaches for permeability determination from logs from a practical point of view. The three methods, empirical, statistical, and the recently introduced "virtual measurement," make use of empirically determined models, multiple variable regression, and artificial neural networks, respectively. We apply all three methods to well log data from a heterogeneous formation and compare the results with core permeability, which is considered to be the standard. Our comparison f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(49 citation statements)
references
References 14 publications
0
43
0
2
Order By: Relevance
“…These algorithms include multiple linear regression (Dahraj and Bhutto 2014;Mohaghegh et al 1997;Xue et al 1997), generalized additive modeling (Al-Mudhafar and Mohamed 2015; AlMudhafar and Bondarenko 2015; Lee et al 2002;Rafik and Kamel 2016), multivariate adaptive regression splines (Al-Mudhafar and Al-Khazraji 2016;Xie 2008), neural networks (Lee and Datta-Gupta 1999;Lee et al 2002;Mohaghegh et al 1997), fuzzy logic (Nashawi and Malallah 2009), and support vector regression (Al-Anazi and Gates 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These algorithms include multiple linear regression (Dahraj and Bhutto 2014;Mohaghegh et al 1997;Xue et al 1997), generalized additive modeling (Al-Mudhafar and Mohamed 2015; AlMudhafar and Bondarenko 2015; Lee et al 2002;Rafik and Kamel 2016), multivariate adaptive regression splines (Al-Mudhafar and Al-Khazraji 2016;Xie 2008), neural networks (Lee and Datta-Gupta 1999;Lee et al 2002;Mohaghegh et al 1997), fuzzy logic (Nashawi and Malallah 2009), and support vector regression (Al-Anazi and Gates 2011).…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table 3, the multiple (variable) regression coefficients (R) of the three mathematical models are high and they all indicate good relationship between the dependent and independent variables (Mohaghegh et al, 1997;Wendt et al, 1986). The significance F values of the three models are less than 0.0005 which indicates that they are statistically significance.…”
Section: Prediction Of Petrophysical Properties Of D3 Reservoir Intermentioning
confidence: 93%
“…The dependent variables are permeability, R35 and flow zone indicators, while bulk density and gamma ray log data were used as predictor or independent variables because the two parameters reflect variations in permeability and porosity (Dewan, 1983). The theory of multiple regression analysis can be found in (Draper and Smith, 1998;Mohaghegh et al, 1997;Wendt et al, 1986;Orlov, 1996).…”
Section: Dataset and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mohaghegh et al (1997) presented a comparison of empirically determined models, multiple variable regressions, and ANN, and showed that ANN resulted in better performance than the other methods. Lim and Kim (2004) demonstrated that fuzzy logic and ANN can be utilized as a powerful tool to determine reservoir properties from well logs.…”
Section: Introductionmentioning
confidence: 99%